Morphological and molecular diagnosis of the pine processionary moth in Marmara University Göztepe Campus - GÖKALSIN, BARIŞ; SESAL, NÜZHET CENK; TURAN, YAVUZ (My University, 2024)
Pine processionary moth are known as oligophagous forest pests, usually found in cocoons on Pinus trees. While these moths are found in the south of Europe and the north of Africa worldwide, in Turkey they are found in the Mediterranean, Aegean, Black Sea and Marmara regions. Thaumetopoea pityocampa (Den. & Schiff.) and Thaumetopoea wilkinsoni (Tams) species have been observed in the coastal regions of Turkey. Identification of the species is an important step in the development of biological control strategies. The starting point of this study is the desire to control the pine processionary moth in Marmara University Göztepe Campus. However, since both of these species are found in Turkey, especially in the Marmara Region, the main aim of this study is to determine which species the pine processionary moth in the campus belong to. Morphological and molecular methods were used. As a result of the study, based on both morphology and molecular data, it was determined that the species found on the campus was Thaumetopoea wilkinsoni. Keywords: Marmara University, Molecular Systematics, Morphology, Pine Processionary Moth, Thaumetopoea wilkinsoni
Keywords: Marmara University; Molecular Systematics; Morphology; Pine Processionary Moth; Thaumetopoea wilkinsoni